Outcomes of cardiac screening in New Zealand Football - Davis, A.; Gray, B.; Driscoll, T.; Orchard, J.; Hamilton, B.; Doughty, R.; Fulcher, M.; Orchard, J. (Journal of Science and Medicine in Sport, 2024)
Introduction: Cardiac screening of elite footballers for conditions associated with sudden cardiac arrest/death (SCA/D) is a requirement of Fédération Internationale De Football Association (FIFA). Cardiac screening must be completed before an athlete competes in a FIFA tournament as a key aspect of pre-competition medical assessment (PCMA). This study aimed to report the findings, cardiac diagnoses, and outcomes from the New Zealand Football (NZF) screening program for FIFA tournaments since 2012, and to compare echocardiograms with other part of screening. Methods: This was a retrospective cohort study of female and male footballers from NZF who were screened for a FIFA event from January 2012 to November 2023. Footballers were screened with a personal/family history, physical examination, resting 12-lead electrocardiogram (ECG) and transthoracic echocardiogram. Abnormal findings were followed-up at the time as needed. An audit (March 2024) reviewed screening records, comprising ECGs, echocardiograms, demographic data, follow-up testing, and diagnoses. A footballer was included if sufficient details about the screening outcome, an ECG trace, and an echocardiogram report in English was available. If a footballer had multiple screenings, only the first was included. ECGs were reviewed using the International Criteria for Athlete ECGs (2017). To assess differences between female and male football players, independent t-tests and Fisher`s exact tests were used. Results: In total, 147 footballers (60% female, mean age 19.2±3.7 years) were included. There were <5 diagnoses of conditions associated with SCA/D. 4.8% of ECGs were abnormal however no patient was subsequently identified to have underlying structural heart disease on echocardiography. Female footballers were less likely than men to have left ventricular hypertrophy (LVH) according to voltage criteria (8.4% vs 37.8% respectively, p<0.001), and early repolarisation (4.5% vs 35.6%, p<0.001). There were no sex differences in rates of abnormal ECG findings or abnormal T-wave inversion. In echocardiograms, females had significantly lower indexed left ventricular end diastolic volumes (61.9±8.8 ml/m2 vs 74.3±12.9 ml/m2, p<0.001), and indexed left ventricular end systolic volumes (22.1±5.5 ml/m2 vs 29.7±6.9 ml/m2, p<0.001). When comparing echocardiogram with other findings, LVH by voltage criteria on ECG did not correlate with LVH on echocardiogram. Six footballers had audible murmurs on physical examination; only one of these was among the 20 footballers who had valve regurgitation on echocardiogram. No athletes retired for cardiac reasons and there were no incidents of SCA/D during the period. Discussion: This cohort had similar findings to other football populations. Some sex differences were found that have been shown in other football cohorts including females with lower indexed ventricular volumes and a lower proportion of normal athlete adaptations to exercise. Sex differences between rates of abnormal ECGs and abnormal T-wave inversion have been found in other football cohorts but not in this cohort. While echocardiograms detected some cases of mild valvular regurgitation, they did not increase the yield of diagnoses associated with SCA/D. Impact/Application to the field: This study showed that cardiac screening at New Zealand football was comparable to other football cohorts. Declaration: MF is the Medical Director of New Zealand Football.